Novel approaches for the rational design of PROTAC linkers - Almaz Zagidullin; Vasili Milyukov; Albert Rizvanov; Emil Bulatov (Open Exploration Publishing Inc., 2020)
Proteolysis targeting chimeras (PROTACs) represent a promising class of hetero-bivalent molecules that facilitate ubiquitination of a target protein by simultaneously binding and bringing together both the E3 enzyme and the target. These compounds consist of three structural components: two ligands one of which binds the protein of interest (POI) while the other binds an E3 ubiquitin ligase to promote POI ubiquitination, and a linker connecting both moieties. Recent developments in the field highlight the fact that linker composition and length play a crucial role in achieving optimal PROTAC properties, modulate binding kinetics and substantially impacts the potency and selectivity. In this review, the authors briefly discuss the recent findings in PROTAC design approaches with focus on the linker. For each PROTAC such linker parameters as chemical nature, length, hydrophilicity and rigidity have to be optimized to achieve improved stability, bioavailability cell membrane permeability and suitable spatial orientation between the target POI and the E3 ubiquitin ligase. Thus rational linker design with respect to composition, length and attachment sites is essential for the development of potent PROTAC compounds. Computer-aided design and novel innovative linker strategies, such as PROTAC shortening, photo-switchable PROTACs, in-cell click-formed CLIPTACs, "click chemistry" approaches are also discussed in the review.